Improving Access to Preconception Care for Women with Severe and Enduring Mental Illness, Through Creation of a Perinatal MDT Clinic in a Rehabilitation Psychiatry Setting - Elizabeth Ashley; Jessica Foster; Sarah Fitch; Katie Fergus; Amy Sheppard (BJPsych Open, 2025)
Aims: Preconception planning is an essential component of improving maternal and child health, particularly for individuals with mental health conditions. Within this population those with severe and enduring mental illnesses face significant barriers to accessing preconception care and are at higher risk of unplanned pregnancy, leading to suboptimal outcomes for both mothers and babies. This poster outlines the establishment of a preconception planning clinic for individuals within a mental health rehabilitation setting, developed through a collaborative initiative between the Rehabilitation and Recovery Service, Perinatal Mental Health Service, All Wales Psychiatric Genomics Service and Sexual Health services.